Degradation Model for the Tensile Strength of PVC and Rubber Gasket Materials Exposed to Benzene and PCE-Saturated Aqueous Solutions. Issue 2 (February 2020) - Hosseini, Payam; Alhomair, Sultan; Faeli, Zahra; Pour-Ghaz, Mohammad; Gabr, Mohammed; Knappe, Detlef; Parker, Cyrus
In this paper, a tensile strength degradation model is developed for polyvinyl chloride (PVC) pipe and three rubber gasket materials commonly used in stormwater drains and wet utilities; the degradation model considers exposure to a single contaminant at its saturation level. The contaminant considered included benzene and tetrachloroethylene (PCE) because of their prevalence. The materials considered are unplasticized Polyvinyl chloride (u-PVC) utilized as the pipe material, and three types of rubber gaskets: Polychloroprene (Neoprene-CR), Acrylonitrile (nitrile) butadiene rubber (Buna-N), and fluoroelastomer rubber (FKM—Grade A Viton TM ). First, the degradation rates of these materials are experimentally quantified using accelerated testing; then using the experimental results and Williams–Landel–Ferry (WLF) method a degradation model is developed. Finally, a simplified method is introduced to relate the tensile strength degradation of PVC to the penetration rate of the contaminants.